Efeito de temperaturas de armazenamento e de genótipos de Feijoeiro sobre a resistência a Acanthoscelides obtectus (say) (Coleoptera: Bruchidae) - Baldin, Edson L.L.; Lara, Fernando M. [UNESP] (My University, 2004)
Aiming to evaluate the effect of different temperatures of storage and bean genotypes, Phaseolus vulgaris L., on the expression of resistance to the bean weevil, Acanthoscelides obtectus (Say), tests were carried out with the genotypes Arc.1S, Arc.1, Arc.2, Arc.4 and Carioca Pitoco. Grains of Arc.1S and Arc.2 expressed resistance to A. obtectus at 20°C, 25°C and 30°C; the resistance of Arc.1 was reduced as the storage temperature increased from 25°C to 30°C. The interaction genotypes x temperatures was significant, indicating that the increase of temperature affects the expression of resistance. The 20°C temperature was the most suitable to allow bean genotypes to be discriminate in terms of resistance.
Effect of storage temperature and bean genotypes on the resistance to acanthoscelides obtectus (say) (Coleoptera: Bruchidae)
Keywords: Bean weevil; Insecta; Phaseolus vulgaris; Plant resistance; Temperature effect